Strategi Pemasaran Pimpinan dalam Meningkatkan Minat Santri untuk Mendaftar di Pondok Pesantren Darul Arifin Jambi - Arvenita, Adella Yulinda; Jannah, Siti Raudhatul; Summiyani, Summiyani (Jurnal Pendidikan Madrasah, 2026)
This study is grounded in the importance of educational marketing strategies in enhancing public interest in Islamic boarding schools. It aims to examine the marketing strategies implemented by the leadership of Darul Arifin Islamic Boarding School in Jambi to increase new student enrollment, as well as to identify supporting and inhibiting factors. The study employs a qualitative approach with a descriptive method, utilizing observation, in-depth interviews, and documentation for data collection. The findings reveal that the strategies include early enrollment opening, optimization of social media as a digital promotion tool, and strengthening institutional image. Meanwhile, constraints include limited human resources, unclear status of some teachers, and increasing competition among Islamic boarding schools. These strategies contribute to higher enrollment rates, improved public trust, and stronger institutional competitiveness.